MORPHOLOGICAL CHANGES IN THE APPENDIX IN EXPERIMENTAL NICOTINE-ALCOHOLIC INTOXICATION - Murtazaev Nodirjon Ismatovich (World Scientific Research Journal, 2025)
During postnatal development, the intensity of glandular-lymphoid relationships in the walls of the cecum changes. Both in and near the cecal-ascending sphincter, lymphoid nodules are occasionally detected near the colonic glands during the neonatal period (approximately 15-20% of histological specimens). Diffuse lymphoid tissue near the glands during this period is determined by the presence of isolated lymphoid cells located near the basal portion of the glands. This article focuses on age-related morphological changes in the cecum in experimental nicotine-alcohol intoxication.